Improvisation in academic management: a case study in a Brazilian public university - Silva, Arthur; Pascuci, Lucilaine; Meyer Jr., Victor (Revista de Negócios, 2023)
In this study, manifestations of improvisation and its relevance to academic management in a public university were analyzed. The study focused on managerial practices carried out by academic program coordinators. This is a qualitative case study that was based on concepts related to decision making in public administration, university management and organizational improvisation. Data were collected through participant observation, ethnographic interviews and documents, which were analyzed through document and narrative analysis. The results showed that the predominant types of improvisation were ad-hoc and covert, with the latter being due to the strong influence of informality. Other characteristcs such as pressure to meet deadlines, experience and creativity were key factors in the improvisational practices identified. Conclusions revealed that improvisational practices were found in the managerial practices of academic coordinators, contributing to not only to solve unexpected problems but also to improve the academic managerial performance.